Transparent glaze and preparation method thereof, ceramic tile and preparation method thereof
By adjusting the content and ratio of alumina and silicon oxide, a transparent glaze was prepared, which contains glass phase and corundum crystal phase, which solves the problem of insufficient wear resistance of existing transparent glazes, achieves high transparency and good wear resistance, and is suitable for dark ceramic tiles.
Patent Information
- Application Number
- CN202411822699.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The transparent glaze on existing glazed tiles is not wear-resistant, especially in dark-colored series products, which are prone to scratches and surface crystallization leads to turbidity, affecting transparency.
By adjusting the content and ratio of alumina and silicon oxide, a transparent glaze was prepared. The mass ratio of SiO2 to Al2O3 in its chemical composition was (3.1~4.2):1, and it contained 95%~97% glass phase and 3%~5% corundum crystal phase.
It achieves high transparency and good wear resistance of transparent glaze, which can meet the requirements of dark ceramic tiles for transparency and wear resistance, while avoiding crystallization and maintaining the clear and transparent glaze surface.
Smart Images

Figure CN119285231B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a transparent glaze and a preparation method thereof, a ceramic tile and a preparation method thereof. Background Art
[0002] Polished porcelain glazed tiles (glazed tiles) are popular among consumers because they have a layer of transparent glaze (glazed tiles) applied on the pattern layer. After being fired and polished, the products can present rich pattern colors and gloss effects. However, the glaze layer on the existing glazed tiles is mainly glass phase, which has high transparency but is not wear-resistant, making the glazed tiles easy to scratch. In particular, dark series products require a more transparent glaze layer effect on the surface, so that the ink color texture effect of the dark layout pattern can be presented. Most of the glazed layers or transparent glaze layers currently used are realized by a higher silicon-aluminum ratio, usually setting the aluminum oxide content below 10% and the silicon dioxide content above 50%. Although this method can achieve the transparency of the glazed layer, the setting of too low aluminum content will cause insufficient wear resistance; there is also a way to increase the aluminum content to improve the surface wear resistance, but it is easy to cause crystallization, causing the glaze layer to be turbid and reduce the surface visual effect. Especially for dark products, it is obvious that the phenomenon of haziness appears. In addition, in order to improve the wear resistance of the glaze, the existing technology also achieves this by adding wear-resistant media such as corundum and zircon sand, but these substances easily cause the glaze to become opaque or because the highly refractory substances increase the temperature of the glaze, the amount of addition is very limited; in response to the problem of excessive glaze temperature caused by wear-resistant media, existing technicians have tried to reduce this limitation by adding nano-sized wear-resistant media. However, in actual production, due to the small particle size of the nano-scale medium, it is very easy to produce a low-temperature eutectic reaction in a firing environment containing alkali metal oxides, and finally more surface crystallization is formed, causing the glaze to become opaque and affecting transparency.
[0003] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a transparent glaze and a preparation method thereof, a ceramic tile and a preparation method thereof, aiming to solve the defect that the transparent glaze currently used on dark ceramic tiles has insufficient wear resistance.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A transparent glaze, wherein in the chemical composition of the transparent glaze, the mass ratio of SiO2 to Al2O3 is (3.1-4.2):1, and the transparent glaze contains 95wt%-97wt% of a glass phase and 3wt%-5wt% of a corundum crystal phase.
[0007] The chemical composition of the transparent glaze includes, by mass percentage, SiO2 45% to 49.5%, Al2O3 12% to 14.5%, CaO 11% to 13%, K2O 4.4% to 5.35%, Na2O 1% to 1.6%, SrO 2.4% to 3.2%, BaO 2.1% to 2.7%, ZnO 7% to 8%, and the remainder is loss on ignition.
[0008] In the transparent glaze, the raw materials for preparing the transparent glaze include, by weight: 31-37 parts of potassium feldspar, 7-9 parts of kaolin, 11.5-14.5 parts of wollastonite, 7-9 parts of calcite, 4.5-5.5 parts of quartz powder, 2.5-3.5 parts of corundum powder, 13.5-16.5 parts of frit, 3.5-4.5 parts of strontium carbonate, 3.5-4.5 parts of barium sulfate, and 5-7 parts of zinc oxide.
[0009] In the transparent glaze, the content of SiO2 in the quartz powder is greater than 99%; the content of Al2O3 in the corundum powder is greater than 99%, and the particle size of the corundum powder is 5µm~10µm.
[0010] In the transparent glaze, the frit includes the following chemical components by mass percentage: SiO2 57-62%, Al2O3 7.7-9%, CaO 10-12.5%, K2O 6.6-7.8%, Na2O 0.5-0.9%, BaO 1%-1.6%, ZnO 9%-12%, and the remainder is the loss on ignition.
[0011] In the transparent glaze, the raw materials for preparing the frit include, by weight: 57-63 parts of potassium feldspar, 2-4 parts of kaolin, 3-5 parts of quartz, 18-20 parts of calcium carbonate, 1-3 parts of barium carbonate, and 10-14 parts of zinc oxide.
[0012] In the transparent glaze, the raw materials for preparing the transparent glaze also include water, a binder, a suspension stabilizer and a preservative.
[0013] A method for preparing a transparent glaze, wherein the method is used to prepare the transparent glaze as described above, and the method comprises the following preparation steps:
[0014] Step 1: Take the raw material components of the transparent glaze by weight and mix them evenly;
[0015] Step 2: Take 100 parts of the mixed raw materials, add 34 parts of water, 0.15 parts of methylcellulose, 0.35 parts of sodium tripolyphosphate, and 0.2 parts of benzoic acid preservatives, ball mill for 12 hours, pass through a 325-mesh sieve, and measure the sieve residue to be 0.5%; then pass through a 325-mesh sieve and age for 36 hours to obtain a transparent glaze slurry with a specific gravity of 1.90±0.02g / cm 3 , flow rate is 32±2s;
[0016] Step 3: After glazing and firing, a layered transparent glaze is formed.
[0017] A ceramic tile comprises a base, a base glaze layer, a pattern layer and a surface glaze layer, wherein the surface glaze layer is the transparent glaze as described above.
[0018] A method for preparing a ceramic tile, used for preparing the ceramic tile as described above, the method comprising the steps of:
[0019] Step 1, forming a bottom glaze layer on the bottom blank;
[0020] Step 2, forming a pattern layer on the base glaze layer;
[0021] Step 3, forming a transparent glaze layer on the pattern layer;
[0022] Step 4: Firing.
[0023] Beneficial effects:
[0024] The first aspect of the present invention provides a transparent glaze. The transparent glaze forms 95wt%~97wt% glass phase and 3wt%~5wt% corundum crystal phase by adjusting the content and ratio of aluminum oxide and silicon oxide. The glass phase can make the transparent glaze have higher transparency and can fully display the pattern texture of dark ceramic tiles, while the corundum crystal phase can make the transparent glaze have better wear resistance and meet the wear resistance requirements of brick surfaces.
[0025] The second invention of the present invention provides a method for preparing a transparent glaze, wherein the method comprises mixing, ball-milling, sieving, aging, glazing and firing the raw materials of the transparent glaze to obtain a layered transparent glaze.
[0026] The third aspect of the present invention provides a ceramic tile, which uses the aforementioned transparent glaze as a surface glaze layer, and thus has high transparency and wear resistance, thereby meeting the requirements of dark ceramic tiles for transparency and wear resistance.
[0027] A fourth aspect of the present invention provides a method for preparing a ceramic tile, wherein a transparent glaze layer is formed on a pattern layer and then fired to obtain a ceramic tile having a transparent glaze layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the phase diagram of the transparent glaze described in Example 1.
[0029] Figure 2 This is a real picture of a dark ceramic tile to which the transparent glaze described in Example 1 is applied. DETAILED DESCRIPTION
[0030] The present invention provides a transparent glaze and a preparation method thereof, a ceramic tile and a preparation method thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail by the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] In view of the defect of the existing polishing glaze layer that the wear resistance is poor when the transparency is high, the first aspect of the present invention provides a transparent glaze. In the chemical composition of the transparent glaze, the mass ratio of SiO2 to Al2O3 is (3.1~4.2):1, wherein the content of Al2O3 is relatively high, and part of Al2O3 exists in the corundum crystal phase, and part of Al2O3 exists in the glass phase, so that the transparent glaze contains 3wt%~5wt% of the corundum crystal phase and 95wt%~97wt% of the glass phase. The glass phase can make the transparent glaze have a higher transparency and can fully display the pattern texture of the dark ceramic tile, while the corundum crystal phase can make the transparent glaze have better wear resistance and meet the wear resistance requirements of the brick surface.
[0032] In a preferred embodiment, the chemical composition of the transparent glaze includes, by mass percentage: SiO2 45%-49.5%, Al2O3 12%-14.5%, CaO 11%-13%, K2O 4.4%-5.35%, Na2O 1%-1.6%, SrO 2.4%-3.2%, BaO 2.1%-2.7%, ZnO 7%-8%, and the remainder is the loss on ignition. In the transparent glaze of this chemical composition, the content of silicon, aluminum and calcium is relatively high, and a relatively high content of glass phase can be formed. When the content of Al2O3 is greater than 10%, the glaze layer can still be clean and transparent, and the transparency of the transparent glaze can reach more than 89%; and the part of Al2O3 existing in the corundum crystal phase can greatly improve the wear resistance of the transparent glaze, so that the wear resistance of the transparent glaze reaches more than level 3.
[0033] In order to obtain the above-mentioned transparent glaze with silicon-aluminum ratio and specific glass phase and corundum crystal phase, in a preferred embodiment, the raw materials for preparing the transparent glaze include, by weight: 31-37 parts of potassium feldspar, 7-9 parts of kaolin, 11.5-14.5 parts of wollastonite, 7-9 parts of calcite, 4.5-5.5 parts of quartz powder, 2.5-3.5 parts of corundum powder, 13.5-16.5 parts of frit, 3.5-4.5 parts of strontium carbonate, 3.5-4.5 parts of barium sulfate, and 5-7 parts of zinc oxide. After the raw materials with this composition are prepared, a transparent glaze with the above-mentioned chemical composition and glass phase and corundum crystal phase can be obtained, which has good transparency and wear resistance.
[0034] In order to improve transparency, reduce defects, and improve wear resistance, among the raw materials for preparing the transparent glaze, the content of SiO2 in the quartz powder is greater than 99%, which is high-purity quartz powder; the content of Al2O3 in the corundum powder is greater than 99%, which is also high-purity, and the particle size of the corundum powder is 5µm~10µm, which can be evenly dispersed in the glass phase; the chemical composition of the frit is: SiO257~62%, Al2O37.7~9%, CaO 10~12.5%, K2O 6.6~7.8%, Na2O 0.5~0.9%, BaO1%~1.6%, ZnO 9%~12%, and the remainder is the ignition loss, which is a frit with high transparency. Therefore, in this embodiment, by using high-purity quartz raw materials and transparent frits with high silicon oxide content, during the firing process, under the action of strong fluxes such as strontium carbonate, barium sulfate, and zinc oxide, a large amount of quartz glass can be directly and quickly melted out to improve transparency. In addition, since this process does not require decomposition reaction, the generation of pores during the melting process can be reduced, making the transparent glaze less flawed, cleaner and more transparent, while having high surface hardness and better anti-fouling effect. The corundum powder is the main source for obtaining the corundum crystal phase. The corundum powder with an alumina content of more than 99% is purer and free of impurities, which can ensure the transparency of the transparent glaze. In addition, the corundum powder with a high alumina content has better high melting properties, so that the corundum powder does not undergo a low eutectic reaction during the firing process to form a corundum phase; at the same time, the corundum powder with a particle size of 5µm~10µm has a large specific surface area and will not undergo a low-temperature eutectic phenomenon. It can be evenly dispersed in the glaze, greatly improving the wear resistance of the glaze; in addition, small-particle-size and high-purity corundum crystals have small scattering and high refractive index, and present high transparency, which can improve the wear resistance while keeping the transparency unaffected. In addition, the added calcite can greatly increase the calcium content in the transparent glaze. The high calcium content can increase the reaction viscosity of the glaze during the firing process. The high reaction viscosity can prevent the crystalline particles from diffusing and migrating, and the crystal nuclei from forming and growing, and crystallization will not occur. The exhaust rate during the firing process can be greatly improved, making the glaze layer as a whole transparent and flawless, with sufficient glass phase, high density of the glaze layer, good strength and hardness, and good acid and alkali resistance.
[0035] In a preferred embodiment, the raw materials for preparing the transparent glaze also include water, a binder, a suspension stabilizer and a preservative. These ingredients can make the aforementioned transparent glaze raw materials be adjusted into a glaze slurry that meets the requirements, which is convenient for glazing on the surface of the base.
[0036] In a preferred embodiment, the raw materials for preparing the frit include, by weight: 57-63 parts of potassium feldspar, 2-4 parts of kaolin, 3-5 parts of quartz, 18-20 parts of calcium carbonate, 1-3 parts of barium carbonate, and 10-14 parts of zinc oxide. The frit raw materials of this component can be used to prepare a frit of the aforementioned chemical composition, which has high transparency and high silicon oxide content, and can react with quartz powder to obtain quartz glass under the fluxing effect of a strong flux, thereby increasing the amount of glass phase and thus improving transparency.
[0037] The second aspect of the present invention also discloses a method for preparing a transparent glaze, the method comprising the following preparation steps:
[0038] Step 1: Take the following transparent glaze raw material components by weight and mix them evenly;
[0039] Step 2: Take 100 parts of the mixed raw materials, add 34 parts of water, 0.15 parts of methylcellulose, 0.35 parts of sodium tripolyphosphate, and 0.2 parts of benzoic acid preservatives, ball mill for 12 hours, pass through a 325-mesh sieve, and measure the sieve residue to be 0.5%; then pass through a 325-mesh sieve and age for 36 hours to obtain a transparent glaze slurry with a specific gravity of 1.90±0.02g / cm 3 , flow rate is 32±2s;
[0040] Step 3: Apply transparent glaze slurry to the brick. After firing, a layer of transparent glaze is formed on the surface of the brick.
[0041] The third aspect of the present invention also provides a ceramic tile, which includes a base, a base glaze layer, a pattern layer and a surface glaze layer, but is not limited to the aforementioned layered structure. The pattern layer can be a dark pattern layer or a light pattern layer, and the surface glaze layer is a transparent glaze as described above, which has good transparency and wear resistance, so it can better display the pattern texture of the pattern layer, has a good decorative effect, and can meet the wear resistance requirements.
[0042] The fourth aspect of the present invention also provides a method for preparing a ceramic tile, the method for preparing the ceramic tile comprising the steps of:
[0043] Step 1, forming a bottom glaze layer on the bottom blank;
[0044] Step 2, forming a pattern layer on the base glaze layer;
[0045] Step 3: forming a transparent glaze layer on the pattern layer, wherein the glaze material used in the transparent glaze layer is the aforementioned transparent glaze material;
[0046] Step 4: Firing.
[0047] The ceramic tile surface obtained by the preparation method has a transparent glaze. Since the transparent glaze has good transparency, the pattern texture of the ceramic tile can be fully displayed. At the same time, since the transparent glaze has good wear resistance, the wear resistance of the ceramic tile can be improved.
[0048] To further illustrate the transparent glaze and its preparation method, ceramic tile and its preparation method provided by the present invention, the following examples are provided.
[0049] Example 1
[0050] A transparent glaze, the preparation method of which is as follows:
[0051] Step 1: Take the following raw material components by weight and mix them evenly: 34 parts of potassium feldspar, 8 parts of kaolin, 13 parts of wollastonite, 8 parts of calcite, 5 parts of quartz powder, 3 parts of corundum powder, 15 parts of frit, 4 parts of strontium carbonate, 4 parts of barium sulfate, and 6 parts of zinc oxide;
[0052] Step 2: Take 100 parts of the mixed raw materials, add 34 parts of water, 0.15 parts of methylcellulose, 0.35 parts of sodium tripolyphosphate, and 0.2 parts of benzoic acid preservatives, ball mill for 12 hours, pass through a 325-mesh sieve, and measure the sieve residue to be 0.5%; then pass through a 325-mesh sieve and age for 36 hours to obtain a transparent glaze slurry with a specific gravity of 1.90±0.02g / cm 3 , flow rate is 32±2s (Tu-4 viscosity cup);
[0053] Step 3: Apply transparent glaze slurry on the pattern layer. After firing, a layer of transparent glaze is formed on the surface of the pattern layer.
[0054] The chemical composition of the transparent glaze is as follows by mass percentage: SiO2 47.2%, Al2O3 13.2%, CaO 11.9%, K2O 4.9%, Na2O 1.3%, SrO 2.8%, BaO 2.4%, ZnO 7.4%, ignition loss and impurities 8.9%; the mass ratio of SiO2 to Al2O3 in the chemical composition is 3.58:1; and, through phase analysis (see Figure 1 ), the mass percentage content of the glass phase in the transparent glaze is 96%, and the mass percentage content of the corundum crystal phase is 4%.
[0055] Example 2
[0056] A transparent glaze, the preparation method of which is basically the same as that of Example 1, except that: in step 1, the raw material components are: 31 parts of potassium feldspar, 9 parts of kaolin, 11.5 parts of wollastonite, 7 parts of calcite, 5.5 parts of quartz powder, 3.5 parts of corundum powder, 13.5 parts of frit, 4.5 parts of strontium carbonate, 3.5 parts of barium sulfate, and 7 parts of zinc oxide.
[0057] The chemical composition of the transparent glaze is as follows by mass percentage: SiO2 49.37%, Al2O3 12.18%, CaO 11.09%, K2O 4.54%, Na2O 1.12%, SrO 3.16%, BaO 2.15%, ZnO 7.83%, loss on ignition and impurities 8.56%; the mass ratio of SiO2 to Al2O3 in the chemical composition is 4.05:1.
[0058] Example 3
[0059] A transparent glaze, the preparation method of which is substantially the same as that of Example 1, except that: in step 1, the raw material components are: 37 parts of potassium feldspar, 7 parts of kaolin, 14.5 parts of wollastonite, 9 parts of calcite, 4.5 parts of quartz powder, 2.5 parts of corundum powder, 16.5 parts of frit, 3.5 parts of strontium carbonate, 4.5 parts of barium sulfate, and 5 parts of zinc oxide;
[0060] The chemical composition of the transparent glaze is as follows by mass percentage: SiO2 45.35%, Al2O3 14.41%, CaO 12.77%, K2O 5.23%, Na2O 1.56%, SrO 2.48%, BaO 2.62%, ZnO 7.07%, loss on ignition and impurities 8.51%; the mass ratio of SiO2 to Al2O3 in the chemical composition is 3.15:1.
[0061] Comparative Example 1
[0062] A polishing glaze, the preparation method of which is basically the same as that of Example 1, except that: step 1, taking the following raw materials by mass percentage and mixing them evenly: 29 parts of potassium feldspar, 10 parts of kaolin, 10 parts of wollastonite, 6 parts of calcite, 6.5 parts of quartz powder, 4.5 parts of corundum powder, 18 parts of frit, 5.5 parts of strontium carbonate, 2.5 parts of barium sulfate, and 8 parts of zinc oxide;
[0063] The chemical composition of the glaze is as follows by mass percentage: SiO2 52.19%, Al2O3 10.51%, CaO 10.02%, K2O 3.93%, Na2O 0.78%, SrO 3.56%, BaO 1.97%, ZnO 8.53%, loss on ignition and impurities 8.51%; the mass ratio of SiO2 to Al2O3 in the chemical composition is 4.97:1.
[0064] Comparative Example 2
[0065] A polishing glaze, whose preparation method is basically the same as that of Example 1, except that: in step one, the raw material composition of the polishing glaze is, by weight: 39.5 parts of potassium feldspar, 6 parts of kaolin, 16 parts of wollastonite, 10 parts of calcite, 3.5 parts of quartz powder, 1.5 parts of corundum powder, 11.5 parts of frit, 2.5 parts of strontium carbonate, 5.5 parts of barium sulfate, and 4 parts of zinc oxide.
[0066] The chemical composition of the glaze is as follows by mass percentage: SiO2 42.36%, Al2O3 15.93%, CaO 13.91%, K2O 5.8%, Na2O 1.82%, SrO 2.07%, BaO 2.88%, ZnO 6.45%, loss on ignition and impurities 8.78%; the mass ratio of SiO2 to Al2O3 in the chemical composition is 2.66:1.
[0067] Comparative Example 3
[0068] A polishing glaze, which is different from Example 1 only in that the particle size of the corundum powder is ≤4µm.
[0069] Comparative Example 4
[0070] A polishing glaze, which is different from Example 1 only in that the particle size of the corundum powder is ≥11µm.
[0071] It should be noted that in Examples 1-3 and Comparative Examples 1-4, the chemical compositions of the frits, by mass percentage, are: SiO2 60.2%, Al2O3 8.0%, CaO 11.0%, K2O 7.2%, Na2O 0.8%, BaO 1.2%, ZnO 10.3%, and the remainder is loss on ignition.
[0072] Phase analysis
[0073] The transparent glazes of Examples 1-3 and the polished glazes of Comparative Examples 1-4 were subjected to phase analysis. The analysis results are shown in Table 1.
[0074] Table 1. Phase analysis results
[0075]
[0076] Performance Test:
[0077] Abrasion resistance, stain resistance, transparency and surface quality testing
[0078] Test standards: Use the method in GB / T3810.7 to test the surface wear resistance; use the method in GB / T3810.14-2016 to test the surface stain resistance and surface quality; use the GB / T2680-94 architectural glass sunlight direct transmittance determination method to test transparency, and make the glaze slurry into glaze slices and fire them (1mm) to measure the sunlight straight line transmission rate;
[0079] Test samples: The test samples for wear resistance and stain resistance were respectively applied to glazed ceramic tiles using the transparent glazes prepared in Examples 1-3 and the polished glazes prepared in Comparative Examples 1-4 for performance testing.
[0080] The preparation steps of the glazed ceramic tile are: prepare a body and apply a base glaze, then inkjet print a pattern, then apply the transparent glaze slurry prepared in the above Examples 1-3 or the glaze slurry prepared in Comparative Examples 1-4 to the pattern layer and dry it, and then kiln fire it according to conventional methods (the maximum firing temperature is ≤1200°C and the firing time is 38~42min).
[0081] The test results are shown in Table 2 below:
[0082] Table 2. Performance test results
[0083]
[0084] As shown in Table 2, the transparent glaze prepared in Examples 1-3 is applied to ceramic tiles, and the stain resistance level of the ceramic tiles reaches level 5, the wear resistance level is above level 3, and the transparency is above 89%. It has good stain resistance and wear resistance, and the surface is transparent, has good color, and is of high quality. This is mainly because the transparent glaze has a large proportion of glass phase. Therefore, even if the content of aluminum oxide in the transparent glaze is increased and the wear resistance is improved, its transparency does not decrease. In addition, Figure 2 This is the actual effect of applying the transparent glaze described in Example 1 on the dark brick surface with texture. Figure 2 It can be seen that the texture of the brick surface can be clearly displayed, and the transparent glaze on the surface has a strong sense of transparency, good color and high transparency.
[0085] By comparing Example 1 and Comparative Example 1, it is found that the wear resistance and transparency of Comparative Example 1 are lower than those of Example 1. This is because in the glaze of Comparative Example 1, the mass percentage ratio of SiO2 to Al2O3 is too large, and the overall content of alumina is slightly low, resulting in insufficient wear resistance of the glaze surface, and high silicon and low aluminum form a lower temperature eutectic reaction during the firing process, which is prone to form more crystallization, resulting in poor transparency and color development effects.
[0086] By comparing Example 1 and Comparative Example 2, it is found that the wear resistance and transparency of Comparative Example 2 are also lower than those of Example 1. This is because when the mass percentage ratio of SiO2 to Al2O3 is too small, it is difficult to form enough glass phase in the glaze layer, there are more crystal phases and the density is insufficient, the glaze surface is dull, and the transparency and coloring effects are poor.
[0087] By comparing Example 1 and Comparative Example 3, it is found that when the particle size of the corundum powder is too small, it is directly melted into a glass phase by a low-temperature eutectic reaction. The glaze layer has a strong sense of transparency but lacks the presence of corundum crystals, resulting in poor wear resistance.
[0088] By comparing Example 1 and Comparative Example 4, it is found that when the particle size of the corundum powder is too large, the specific surface area is small, and the distribution density of the corundum particles is insufficient, which will also make the surface wear resistance insufficient. At the same time, larger particles are prone to form obvious bumps on the surface, which is not conducive to subsequent polishing.
[0089] It can be seen that the present invention adjusts the content and ratio of aluminum oxide and silicon oxide in the transparent glaze to form a glass phase and a corundum crystal phase in the transparent glaze, which can greatly improve the transparency of the transparent glaze and improve its wear resistance, thereby meeting the requirements of dark ceramic tiles for wear resistance and transparency.
[0090] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and inventive concept of the present invention, and all these changes or substitutions should fall within the protection scope of the claims attached to the present invention.
Claims
1. A transparent glaze, characterized in that: In the chemical composition of the transparent glaze, the mass ratio of SiO2 to Al2O3 is (3.1-4.2):1, and the transparent glaze contains 95wt%-97wt% of glass phase and 3wt%-5wt% of corundum crystal phase; The raw materials for preparing the transparent glaze include, by weight: 31-37 parts of potassium feldspar, 7-9 parts of kaolin, 11.5-14.5 parts of wollastonite, 7-9 parts of calcite, 4.5-5.5 parts of quartz powder, 2.5-3.5 parts of corundum powder, 13.5-16.5 parts of frit, 3.5-4.5 parts of strontium carbonate, 3.5-4.5 parts of barium sulfate, and 5-7 parts of zinc oxide; The content of SiO2 in the quartz powder is greater than 99%; the content of Al2O3 in the corundum powder is greater than 99%, and the particle size of the corundum powder is 5µm~10µm; The frit includes the following chemical components by mass percentage: SiO2 57-62%, Al2O3 7.7-9%, CaO 10-12.5%, K2O 6.6-7.8%, Na2O 0.5-0.9%, BaO 1%-1.6%, ZnO 9%-12%, and the remainder is loss on ignition.
2. The transparent glaze according to claim 1, characterized in that: Measured by mass percentage, the chemical composition of the transparent glaze includes: SiO2 45%~49.5%, Al2O3 12%~14.5%, CaO 11%~13%, K2O 4.4%~5.35%, Na2O 1%~1.6%, SrO 2.4%~3.2%, BaO 2.1%~2.7%, ZnO 7%~8%, and the remainder is loss on ignition.
3. The transparent glaze according to claim 1, characterized in that: In parts by weight, the raw materials for preparing the frit include: 57-63 parts of potassium feldspar, 2-4 parts of kaolin, 3-5 parts of quartz, 18-20 parts of calcium carbonate, 1-3 parts of barium carbonate, and 10-14 parts of zinc oxide.
4. The transparent glaze according to claim 1, characterized in that: The raw materials for preparing the transparent glaze also include water, a binder, a suspension stabilizer and a preservative.
5. A method for preparing a transparent glaze, characterized in that: For preparing the transparent glaze according to any one of claims 1 to 4, the method comprises the following preparation steps: Step 1: Take the raw material components of the transparent glaze by weight and mix them evenly; Step 2: Take 100 parts of the mixed raw materials, add 34 parts of water, 0.15 parts of methylcellulose, 0.35 parts of sodium tripolyphosphate, and 0.2 parts of benzoic acid preservatives, ball mill for 12 hours, pass through a 325-mesh sieve, and measure the sieve residue to be 0.5%; then pass through a 325-mesh sieve and age for 36 hours to obtain a transparent glaze slurry with a specific gravity of 1.90±0.02g / cm 3 , flow rate is 32±2s; Step 3: After glazing and firing, a layered transparent glaze is formed.
6. A ceramic tile comprising a base, a bottom glaze layer, a pattern layer and a top glaze layer, characterized in that: The surface glaze layer is the transparent glaze as described in any one of claims 1-4.
7. A method for preparing a ceramic tile, characterized in that: For preparing the ceramic tile according to claim 6, the preparation method comprises the steps of: Step 1, forming a bottom glaze layer on the bottom blank; Step 2, forming a pattern layer on the base glaze layer; Step 3, forming a transparent glaze layer on the pattern layer; Step 4: Firing.
Citation Information
Patent Citations
Wear-resistant transparent glaze and method for preparing glazed tile by utilizing same
CN105948503A
High-viscosity middle-layer glaze capable of eliminating pinholes in polished glaze surface and polished glaze rock plate using high-viscosity middle-layer glaze
CN113336444A